State space analysis and quick control methods for the series parallel resonant converter. - Chen, Hao. (2010)
Resonant converters have been used as DC/DC power converters in many applications. Compared with hard-switching PWM converters,thesoft-switching resonant converter performs better for higher switching frequency operation. Among different topologies, the Series-Parallel Resonant Converter(SPRC)has one of the most important topology which takes full advantage of the favorable properties and overcomes the limitations of the series resonant converter(SRC)and the parallel resonant converter(PRC). Here, the SPRC is taken as the focus of research. Although resonant converters have many advantages over PWM converters, one key obstacle to their widespread use is their unusual non-linear resonant tank behavior. Such behavior results in an increased output filter size and lower closed-loop bandwidth to switching frequency ratio. If quick and reliable control methods are made available, the draw back can be overcome.